A comparative study on the clinical efficacy of microplate trans-carpometacarpal joint fixation and non-trans-carpometacarpal joint fixation in treating fractures with dislocation or subluxation of the base of the fourth and fifth metacarpal bones - Liang Zhao (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background This study aimed to compare the clinical efficacy of microplate trans-carpometacarpal joint fixation and non-trans-carpometacarpal joint fixation in treating fractures and dislocation or subluxation of the base of the fourth and fifth metacarpal bones. Method From 2015 to 2021, 100 cases of metacarpal basal fractures with dislocation or subluxation were randomly divided into the trans-carpometacarpal joint fixation group (group A) and non-trans-carpometacarpal joint fixation group (group B). Group A (n = 50) comprised 44 males and 6 females, with an average age of 28.8 ± 6.1 y and an Orthopedic Trauma Association (OTA) fracture classification of type B1 (n = 29) or C1 (n = 21). Group B (n = 50) comprised 45 males and 5 females, with an average age of 28.9 ± 5.7 y and an OTA fracture classification of type B1 (n = 28) or C1 (n = 22). All patients were complicated with dislocation or subluxation. The surgery time, fracture healing time, postoperative handgrip strength, and total active motion (TAM) scores of the ring and little fingers were recorded and compared between the two groups. The clinical efficacy of patients was evaluated using scoring methods such as DASH (disabilities of the arm, shoulder and hand), visual analogue scale (VAS), and Mayo at 3, 6, and 12 months after surgery. Results There was no significant difference in the general indexes, surgery time, or fracture healing time between the two groups (P > 0.05). There were no significant differences in handgrip strength and TAM scores of the ring and little fingers between the two groups at 3 and 12 months postoperatively (P > 0.05), but there were significant differences in these indexes 6 months postoperatively (P < 0.05). There were no significant differences in the DASH, VAS, and Mayo scores at 3 and 12 months postoperatively (P > 0.05), but there were significant differences between the two groups in the DASH and Mayo scores (P < 0.05) but not the VAS score (P > 0.05) 6 months postoperatively. Conclusion In the treatment of fourth and fifth metacarpal basal fractures with dislocation or subluxation, both microplate transarticular fixation and non-transarticular fixation could achieve fracture fixation and healing, and each method had advantages and disadvantages. The clinically appropriate fixation method should be selected according to the experience of the surgeon and the degree and type of fracture and dislocation.